Pyrene Excimer Signaling Molecular Beacons for Probing Nucleic Acids - Conlon, Patrick (2007)
Molecular beacon DNA probes, containing one to four pyrene monomers on the 5′ end and the quencher DABCYL on the 3′ end, were engineered and employed for real-time probing of DNA sequences. In the absence of a target sequence, the multiple-pyrene labeled molecular beacons (MBs) assumed a stem-closed conformation resulting in quenching of the pyrene excimer fluorescence. In the presence of target, the beacons switched to a stem-open conformation which separated the pyrene label from the quencher molecule and generated an excimer emission signal proportional to the target concentration. Steady-state fluorescence assays resulted in a sub-nanomolar limit of detection in buffer, while time-resolved signaling enabled low-nanomolar target detection in cell growth media. It was found that the excimer emission intensity could be scaled by increasing the number of pyrene monomers conjugated to the 5′ terminal. Each additional pyrene monomer resulted in substantial increases in the excimer emission intensities, quantum yields, and excited-state lifetimes of the hybridized MBs. The long fluorescence lifetime (~40 ns), large Stokes shift (130 nm), and tunable intensity of the excimer make this multiple-pyrene moiety a useful alternative to traditional fluorophore labeling in nucleic acid probes. In addition, this excimer complex serves as an efficient FRET donor for red-emitting fluorophores, such as TMR, for further extending the Stokes shift of the fluorescent complex.